THE EFFECT OF GAME-BASED LEARNING MODEL ASSISTED BY A BAMBOOZLE ON THE MULTIPLICATION OPERATION SKILLS OF ELEMENTARY SCHOOL STUDENTS - Irma Retno Rahayu; Diki Rukmana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Skills in solving multiplication operations are categorized as very low for second- grade elementary school students. The purpose of the research in this article is to determin the effect of the game-based learning model assisted by "Bamboozle" on the multiplication operation skills of elementary school students at Islamic Elementary School of Al Hidayah in the academic year 2021/2002. The research used experimental quantitative research with a One Group Pretest-Posttest design. The research used a saturated sample as a sampling technique and a test as a data collection method. The results showed that the pre-treatment mean score was 63.33 lower than the post-treatment mean score of 91.90. By using the Wilcoxon test data analysis method, based on 21 study samples all of them have increased from pre-test to post-test with an average score of 11.00. In addition, by looking at the Asymp value. Sig. (2-tailed) 0.000 < 0.05, it could be concluded that there was a significant effect of the implementation of the game-based learning model assisted by the "Bamboozle" on the multiplication operation skills for the second-grade students of SD Islam Al-Hidayah in the academic year 2021/2022.